Modeling the effect of temperature and notch root radius on fracture toughness - Deng, Yong; Zhang, Chao; Shao, Jiaxing; Li, Weiguo (Frontiers in Materials, 2022)
In this work, a physics-based temperature-dependent fracture toughness model without any fitting parameters is established based on the equivalent relationship between the critical strain energy and system’s internal energy. The quantitative relationship between fracture toughness, melting point, Young’s modulus, Poisson’s ratio and temperature is uncovered. Moreover, the effect of notch root radius on fracture toughness is further considered, then we developed a theoretical model to characterize the combined effect of temperature and notch root radius on fracture toughness. Satisfactory agreement between the available experimental measurements and our model predictions is obtained. This study not only advances our in-depth understanding of the quantitative relationship between temperature and fracture toughness, but also provides a powerful and convenient tool to predict the temperature-dependent fracture toughness at different notch root radius.